IFC targets Kenya healthcare through Sh11bn equity - Mutegi, Mugambi (Nairobi Nation media, 2018)
The International Finance Corporation is scouting for investments in Kenya's healthcare sector through a Sh11bn .The fund has investment in healthcare provider AAR Group as well as Carepay Limited
Keywords: Healthcare